Association of Depression with Inflammation in Hospitalized Patients of Myocardial Infarction - Shang, Yu-Xiu (Professional Medical Publicaitons, 2014)
Objective: The aim of this study was to examine the associations between depression and inflammatory markers in patients admitted to the hospital for myocardial infarction. Methods: Inflammatory cytokines, including high-sensitivity C-reactive protein (hs-CRP), interleukin (IL)-1β, IL-6, and tumor necrosis factor-α (TNF-α) were assessed in a group of 75 depressed participants (score of ≥ 12) and compared to a control group of 75 nondepressed participants (score < 12), all who had been admitted to the hospital for myocardial infarction. The presence of depressive symptoms was assessed using the Beck Depressive Symptoms Inventory II Scale (BDI-II). Results: Depressed myocardial infarction participants had significantly greater levels of TNF-α (t = 2.070, P < 0.05) compared with control myocardial infarction participants. The BDI-II score was positively correlated with TNF-α levels (r = 0.222, P < 0.05). Conclusions: These results indicate that the presence of depressive symptoms is positively associated with TNF-α levels among patients who have suffered from myocardial infarction.